A novel approach for preparation of nanocomposites with an excellent rigidity/deformability balance based on reinforced HDPE with halloysite. (7th February 2023) - Cecílio, Duarte M.; Cerrada, Maria L.; Pérez, Ernesto; Fernandes, Auguste; Lourenço, João Paulo; McKenna, Timothy F.L.; Ribeiro, M. Rosário
Graphical abstract: Highlights: Highly performant PE-based hybrid materials reinforced with halloysite nanotubes are prepared. An innovative and straightforward route is applied. A halloysite supported MAO activator and an in situ supporting concept are combined. The ultimate hybrid materials show an excellent rigidity/deformability balance. Increase up to > 70 % in the Young's modulus, while retaining the limit stretching ability of the pristine PE. Abstract: An innovative approach, designated as supported activator (SA), allows preparation of high density polyethylene (HDPE)-based highly performant hybrid materials. This procedure makes use of a nano-sized supported methylaluminoxane (MAO)-activator, based on halloysite natural nanotubes (HNT), combined with an in situ supporting concept. The new protocol when compared with a more conventional approach gives rise to higher polymerization activities as well as ultimate materials with better morphological features, greater crystallinity, thicker crystals, and highly increased stiffness. Moreover, a remarkable synergy between rigidity and toughness is attained. The Young's modulus of a film obtained from the nanocomposite with the highest HNT content increases more than 70 % relatively to a pristine HDPE film, while retaining the limit stretching ability of pristine HDPE (more than 800%). A beneficial impact of using a high aspect ratio support such as HNT in the mechanical properties is also observed, when compared to similar HDPE hybrid materials derived from dendrimer-like silica (DS) nanospheres. Interestingly, polymerization activity, polymer features and derived properties found in the ultimate materials are less impacted by support/filler nature than by preparation method. This fact highlights the crucial role of the synthetic methodology used and corroborates the high potential of the SA route for the preparation of high-performance polyethylene-based nanocomposites with an excellent balance between stiffness and deformability.